Effects of inside-out heat-shock via microwave on the fruit softening and quality of persimmon during postharvest storage. (1st July 2021) - Chen, Yanpei; Zhang, Xiaochen; Luo, Zisheng; Sun, Jian; Li, Li; Yin, Xueren; Li, Jiangkuo; Xu, Yanqun
Highlights: Heat-shock treatments assisted the deastringency and increased the quality of persimmon. Microwave heat-shock delayed fruit softening more significantly than hot water. Microwave treatments curbed the cellulose and pectin degradation and cellulase activity. Microwave heat-shock obviously inhibited the cell-well-degrading genes expression. Abstract: Rapid postharvest softening largely limits the shelf-life of persimmon ( Diospyros kaki L.) fruit. Microwave is a new environmental-friendly inside-out heat-shock approach, whose effect on the fruit softening and quality has not yet been investigated. The current study applied two kinds of microwave treatments (low-power long-time, LPLT, or high-power short-time, HPST) to persimmon fruit with comparison to the hot water (HW) treatments. The results showed both microwave treatments maintained firmness, facilitated the deastringency, and increased soluble solid contents (SSC) and sugar-acid ratio of persimmon fruit. The microwave treatments reduced the cellulose and pectin degradation, and inhibited the cellulase activity, resulting in a significantly higher firmness than HW treatment and control after 2 and 4 days of storage. Moreover, application of HPST treatment down-regulated gene expression of DkPG1, DkPE2 and DkEGase1 compared with untreated fruits. These results indicated that microwave treatment is a promising soft-delaying method for the preservation of persimmon fruit.